2020
DOI: 10.23960/jpmipa/v21i2.pp146-162
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Science in The New Normal: Understanding The Experiences of Junior High School Science Teachers

Abstract: The Covid-19 pandemic has taken aback everyone that led to living unexpectedly in an environment called the new normal. One of the sectors seriously affected by this health crisis is education. With no face-to-face classes until a vaccine has been discovered, the Department of Education-Philippines (DepEd) believed that education should continue in school year 2020-2021 through online and other alternative modalities. The teachers in a private sectarian school in Manila began preparing as early as June 2020 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Additionally, the challenge also came from the less motivated and discouraged students (Arrieta et al, 2020;Fauzani et al, 2021;Fitriyah & Jannah, 2021;Kusuma et al, 2021;Nurkamto et al, 2022;Rachmawati et al, 2022;Wibowo & Novitasari, 2021;Yulianto & Mujtahid, 2021;Zboun & Farrah, 2021). Many students feel less motivated in an online class because they are bored of virtual interaction (Zboun & Farrah, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the challenge also came from the less motivated and discouraged students (Arrieta et al, 2020;Fauzani et al, 2021;Fitriyah & Jannah, 2021;Kusuma et al, 2021;Nurkamto et al, 2022;Rachmawati et al, 2022;Wibowo & Novitasari, 2021;Yulianto & Mujtahid, 2021;Zboun & Farrah, 2021). Many students feel less motivated in an online class because they are bored of virtual interaction (Zboun & Farrah, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Moreover, another challenge found was the internet cost and connection (Arrieta et al, 2020;Kusuma et al, 2021;Nurkamto et al, 2022;Ukhrowiyah et al, 2021;Wibowo & Novitasari, 2021;Widiastuti et al, 2021;Yulianto & Mujtahid, 2021;Zboun & Farrah, 2021). The internet connection problem has still become a hot issue in conducting online learning (Nurkamto et al, 2022;Ukhrowiyah et al, 2021;Yulianto & Mujtahid, 2021).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Getting the students; full interest and attention is also a major obstacle. A study by Arrieta, Dancel, and Agbisit (2020) acknowledged this idea and stated that the nature of asynchronous online learning contains a limited number of strategies that can be suitable for this method. It was also implied that the teachers' prerogative made every learning session interesting and enjoyable for the students.…”
Section: Literature Review Teacher's Approach To Teaching Science Onlinementioning
confidence: 99%
“…In a study on teaching science online, it was found out that the challenges can be overcome by taking initiatives and doing more creative activities that are doable online. Science teachers also see a silver lining in the new normal by becoming more updated and continuously engaging in the new developments in Science for there are better things to come (Arrieta, Dancel & Agbisit, 2020). The global issues related to modern education in high-tech era insist the teachers improve their skills to be in line with the rapid changes of world's needs.…”
Section: Be More Open-mindedmentioning
confidence: 99%